SUNAN KALIJAGA DALAM NOVEL BABAD WALISONGO, WALI SANGA, DAN KISAH DAKWAH WALI SONGO - Erlis Nur Mujiningsih (Fakultas Sastra Universitas Negeri Malang, 2015)
The issues in this research is to provide that novels Wali Sanga by Shashangka, Babad Walisongo by Yudhi Aw, and Kisah Dakwah Wali Songo by Kusuma is the cristalization of discourse interaction in walisongo. The scope of this research is to prove that three novels success to provide the cristalization of discourse interaction in the varians fields that narrative walisongo. Method of this research is qualitative method. Resources of data is novels Babad Walisongo by Yudhi AW, Wali Sanga by Shashangka, Kisah Dakwah Wali Songo by Kusuma. Data this research is words, sentence, and discourse in three novels. To analyze them is used nautical direction and a critic of literature sociology. The results of this research is that two novels worked Wali Sanga by Shashangka and Babad Walisongo by Yudhi Aw can provide the cristalization of discourse interaction in walisongo while, the novel Kisah Dakwah Wali Songo don’t appear that things.